Effectiveness of ceftazidime/avibactam as salvage therapy for treatment of infections due to OXA-48 carbapenemase-producing Enterobacteriaceae. (7th August 2018) - Sousa, Adrian; Pérez-Rodríguez, María Teresa; Soto, Adriana; Rodríguez, Lorena; Pérez-Landeiro, Antonio; Martínez-Lamas, Lucia; Nodar, Andrés; Crespo, Manuel
Abstract: Background: Experience in real clinical practice with ceftazidime/avibactam is limited, and there are even fewer data on infections due to OXA-48-producing Enterobacteriaceae. Methods: We designed an observational study of a prospectively collected cohort of adult patients receiving ceftazidime/avibactam in our centre. Only the first treatment course of each patient was analysed. Efficacy and safety were evaluated as 14 and 30 day mortality, recurrence rate at 90 days, resistance development and occurrence of adverse effects. Results: Fifty-seven patients were treated with ceftazidime/avibactam. The median age was 64 years (range 26–86), 77% were male and the median Charlson index was 3. The most frequent sources of infection were intra-abdominal (28%), followed by respiratory (26%) and urinary (25%). Thirty-one (54%) patients had a severe infection (defined as presence of sepsis or septic shock). Most patients received ceftazidime/avibactam as monotherapy (81%) and the median duration of treatment was 13 days. Mortality at 14 days was 14%. In multivariate analysis, the only mortality risk factor was INCREMENT-CPE score >7 (HR 11.7, 95% CI 4.2–20.6). There was no association between mortality and monotherapy with ceftazidime/avibactam. The recurrence rate at 90 days was 10%. Ceftazidime/avibactam resistance was not detected in any case and only two patients developed adverse events related to treatment. Conclusions: Ceftazidime/avibactam shows promising results, even in monotherapy, for the treatment of patients with severe infections due to OXA-48-producing Enterobacteriaceae and limited therapeutic options. The emergence of resistance to ceftazidime/avibactam was not observed.